Pertanggung Jawaban Rumah Sakit Terhadap Limbah Bahan Beracun Berbahaya (B3) - Egi Agfira Noor (Jurnal Penegakan Hukum Indonesia, 2020)
The purpose of this study was to analyze the hospital's responsibility for medical waste classified as hazardous toxic materials in accordance with the Minister of Environment and Forestry Regulation Number 56 of 2015, and to analyze the legal consequencesfor hospitals if they do not treat medical waste classified as hazardous toxic materials. This research is a normative research. The results of this study: First the responsibility of the hospital for medical waste classified as hazardous toxic materials in accordance with the Minister of Environment and Forestry Regulation Number 56 of 2015. Second, the legal consequences for the hospital if it does not treat medical waste which is classified as hazardous toxic materials is subject to punishment in accordance with the provisions. in Law Number 32 of 2009 concerning Environmental Protection and Management